POLA KOMUNIKASI PADA UPACARA ADAT (STUDI ETNOGRAFI KOMUNIKASI DALAM UPACARA ADAT METATAH DI BALI) - Gusti Ayu Putu Widaratih Puty Pinangkani; Rita Destiwati (Prodi Ilmu Komunikasi FISIP Universitas Langlangbuana, 2017)
Indonesia is a country that has a diversity of cultures and has uniqueness. One of the provinces that has unique is Bali and culture found only in Bali is Metatah Ceremony. Metatah traditional ceremony is a ceremony conducted by parents to their children. The ceremony is held to eliminate bad habbit that exist in man to make it later in the future be better than ever. The study examined the Metatah ceremonies are about the communication patterns that occur in the implementation Metatah ceremonies. To determine the pattern seen in the implementation of traditional ceremonies Metatah seen through three indicators, namely symbolic interaction that occurs between the components of communication, communication activities that occur during an observation implementation Metatah ceremonies and ritual communication that occurs as a function of communication. Overall this study housed within a qualitative ethnographic study methods of communication and using the constructivist paradigm. The data obtained in this study were obtained through field observations, interviews and document study. The results obtained in this study is the relationship between the activity of communication, interaction and communication symbolic ritual to create a pattern of communication called sirkular communicaton pattern of Metatah ceremony.